Experiences of transit: the spectator-walker model in SRE visitas guiadas by Teatro Ojo (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article examines the performance installation S.R.E. Visitas Guiadas (2007), created by the Mexican collective Teatro Ojo, as an example of the configuration of a walker‑spectator model within Mexican theater in the first quarter of the twenty‑first century.  The analysis shows how the installation transforms spectatorship into an embodied and relational practice that emerges from moving through a nodal site of the Mexican urban landscape shaped by layered historical strata. The performances become self‑referential events that rearticulate the relationships between archive and repertoire, personal and collective memory, and produce new understandings of the nation’s past and present.
Keywords: Teatro Rojo; mexican expanded scene; 21st-century Mexican theatre; walker spectator; urban memory